Importancia de los ácidos grasos poliinsaturados de cadena larga en la alimentación del lactante: cuantificación de éstos en algunas fórmulas lácteas para bebés de 0 a 6 meses, comercializadas en la ciudad de Medellín, 2012 (2014)
ABSTRACT: To compare the content of polyunsaturated fatty acids (pufas) appearing in the nutrition facts labels of infant milk formulas sold in supermarkets of Medellin city against an experimentally determined quantity. Methodology: the researchers studied a total of 13 infant initiation formulas collected from the stands where they were displayed at the supermarkets. The procedure for extracting and quantifying the fatty acids in the samples was performed in compliance with the methods developed in the laboratory. Results: upon comparing the content of the pufas displayed in the label of each milk formula with the data obtained experimentally, the researchers found that the products contain less than 30% of the reported values. This variation was not attributable to the expiration date, but to the storage temperature. Discussion: the study's findings are worrisome given the fact that health professionals recommend such products because of the similarity of their nutritional composition with that of breast milk. Moreover, these professionals expect the pufas content to be at least equal to or equivalent to that of breast milk so in order to provide the baby with the necessary nutrients for an appropriate development. For this reason, it is necessary that infant feeding experts strictly regulate the addition of these fatty acids to infant food